2018
DOI: 10.1029/2018ja025680
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solar Activity on Penetration of Traveling Planetary‐Scale Waves From the Troposphere Into the Thermosphere

Abstract: In this study, numerical simulations of planetary‐scale waves (PSWs), generated in the troposphere, were performed for altitudes from the Earth's surface up to 300 km. The influence of thermospheric effects of solar activity (SA) on the amplitudes and phases of westward traveling PSWs with zonal wave numbers 1 and 2 and periods 4–16 days propagating from the troposphere was simulated. Such simulations for a large number of PSW modes in the thermosphere were made for the first time. The effects of SA changes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 99 publications
(118 reference statements)
2
20
1
1
Order By: Relevance
“…The solar cycle dependence of traveling planetary waves is a comparatively understudied field, mainly due to the challenge of obtaining homogeneous measurements on decadal time scales. The few previous studies either focused on the thermosphere/ionosphere, where the wave amplitudes are dominated by the temperature dependence of dissipative processes in the E‐region and tidal‐planetary wave interactions to imprint the planetary wave periods on this altitude regime (e.g., Forbes et al, 2018; Koval et al, 2018), or long‐term radar observations in the mesosphere. The former do not matter for the current question, and the latter are largely focused on the quasi‐2‐day wave (Q2DW) ranging from no correlation at northern midlatitudes (Lilienthal & Jacobi, 2015), to large positive correlation in the meridional wind but negative correlation with the zonal wind at subtropical NH latitudes (Gu et al, 2013), to small negative correlations at the equator (Rao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The solar cycle dependence of traveling planetary waves is a comparatively understudied field, mainly due to the challenge of obtaining homogeneous measurements on decadal time scales. The few previous studies either focused on the thermosphere/ionosphere, where the wave amplitudes are dominated by the temperature dependence of dissipative processes in the E‐region and tidal‐planetary wave interactions to imprint the planetary wave periods on this altitude regime (e.g., Forbes et al, 2018; Koval et al, 2018), or long‐term radar observations in the mesosphere. The former do not matter for the current question, and the latter are largely focused on the quasi‐2‐day wave (Q2DW) ranging from no correlation at northern midlatitudes (Lilienthal & Jacobi, 2015), to large positive correlation in the meridional wind but negative correlation with the zonal wind at subtropical NH latitudes (Gu et al, 2013), to small negative correlations at the equator (Rao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the PWs play an important role in the displacement of the SSW. Many studies have used the EP flux to reveal the magnitude and direction of the energy propagation caused by the PWs (Chen & Huang, ; Harada et al, ; Huang et al, ; Koval et al, ; Leroy & Anderson, ; Portafaix et al, ). The composite EP flux of the quasi 16‐day waves with different wavenumbers at 10 hPa is calculated.…”
Section: Statistical Analysis Of the Quasi 16‐day Waves During Sswsmentioning
confidence: 99%
“…Main characteristics of the Q6DW, including its latitude/height structure and intra‐annual/interannual variability, are well described in the studies mentioned above. Also, general circulation models have been used to examine the excitation and propagation mechanisms of the Q6DW (Liu et al, ; Miyoshi, ; Miyoshi & Hirooka, ) and to quantify the impact on the upper atmosphere (Forbes, Maute, et al, ; Forbes, Zhang, et al, , Gan et al, , ; Koval et al, ; Pedatella et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a follow‐up study (Forbes, Maute, et al, ), they demonstrated that much of planetary wave variability in the ionosphere occurs as a result of such interaction between planetary waves and tides. Koval et al (), also using a numerical model, showed that the vertical extent of westward traveling planetary waves, including the Q6DW, depends on solar activity. They found that planetary wave amplitudes in the thermosphere above 100 km are larger when the solar flux is lower.…”
Section: Introductionmentioning
confidence: 99%